If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + 1) + -1(x + 3) = 35 Reorder the terms: 8(1 + 2x) + -1(x + 3) = 35 (1 * 8 + 2x * 8) + -1(x + 3) = 35 (8 + 16x) + -1(x + 3) = 35 Reorder the terms: 8 + 16x + -1(3 + x) = 35 8 + 16x + (3 * -1 + x * -1) = 35 8 + 16x + (-3 + -1x) = 35 Reorder the terms: 8 + -3 + 16x + -1x = 35 Combine like terms: 8 + -3 = 5 5 + 16x + -1x = 35 Combine like terms: 16x + -1x = 15x 5 + 15x = 35 Solving 5 + 15x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 15x = 35 + -5 Combine like terms: 5 + -5 = 0 0 + 15x = 35 + -5 15x = 35 + -5 Combine like terms: 35 + -5 = 30 15x = 30 Divide each side by '15'. x = 2 Simplifying x = 2
| 39+3m=174 | | 4x+6x+50=20 | | 4x-26=2x+65 | | 42x^3-35x^2+14x=0 | | -7+x=8 | | 2(6v+7)=10(v+8) | | -1/2+3x=1 | | 35+3g=71 | | 8+x/7=16 | | 3x(7)-x=127 | | 6(3n+3)=6(7n+3)+5 | | x^3-8x^2-5x+40=0 | | 15=2m-3 | | 12+x/11=9 | | x(x)+15x=-56 | | 2.2x-2.4=13 | | 3b^2-7b=40 | | m^4+13m^3+22m^2=0 | | x(x)+10x+25=0 | | 3(x-2)+10x=33 | | 12+m/6=15 | | 8y-16+5y=-59 | | s(s)+10s+24=0 | | 7=4x-5 | | 50-2h=44 | | 4x-8=28-x | | -15x=23(4+4)/(-23) | | 4(-7+x)=5x-1/4 | | -15x=23(4+4)/23 | | c/5+8=-5 | | 8/3+2.4 | | 18+9m=288 |